The future belongs to platform enterprises?! The platform business model in Hungary e-commerce - Arany, László; Popovics, Péter András (Studia Mundi – Economica, 2023)
Based on the business and management literature of recent years, the term business model has become an extremely popular phrase. The article discusses the concept, significance and characteristics of the business model of the traditional pipeline and the innovative platform, relying on domestic and international – mainly English-language – literature and databases. As a result of the digitization revolution, alongside traditional linear value chain-based businesses, the rise of platform businesses is indisputable. This article introduces the topic of the business model by defining the enterprise as a fundamental element of the economy, an independent legal person, a separate entity. After defining the characteristics of the enterprise, the significance of the innovative platform business models, the reasons for their rise and the conditions for their growth will be discussed. The comparison between the platform and the pipeline business model basically examines the differences between the two types. Based on the Statista databases, the revenues of the platform economy in the European Union increased nearly fivefold in the period between 2016-2020. They increased from 3 billion EUR to 14 billion EUR. The Hungarian platform economy also contributed to this value. The article explores the accessibility and e-commerce activities of platform companies operating in Hungary in a few segments, with an approach from the consumer (demand) side. Among other things, by e-commerce data in Hungary for the years 2010-2022 (ratio of online-offline stores, sales, online purchases as a percentage of the total population, number of domestic online orders).
Keywords: business model; pipeline; platform; e-commerce; enterprise